Experimental and numerical investigation on penetration of clay masonry by small high-speed projectile. (March 2020) - Wang, C Z; Chen, A J; Li, Z Q; Gong, C A; Wang, S; Yan, W M
Abstract: Masonry is one of the most common building materials, which is used due to low cost, good sound and heat insulation properties, easy availability and locally available material [1]. Masonry walls are consisted of bricks and mortar which interconnect regularly, the bricks are jointed together by the mortar through various conventional patterns. Since its extensive application it would certainly be subjected to a variety of strikes from human activities such as wars and military conflicts apart from erosion of natural forces wind, rain and so on. The knowledge of masonry will be useful if on urban battlefield because of the inability of conventional forces to manoeuvre troops and vehicles with ease. Many reviewer hold that urban warfare is on the increase, with recent events in Iraq, Libya and Syria indicating that the battleground is shifting inexorably to large and small conurbations. Thus it is necessary to work out how to operate in the future urban environment and maximise our capabilities at a time of diminishing military strength [2]. As pointed out by C. S. Meyer, the U.S. Army's concern in urban operations has brought about efforts at the U.S. Army Research Laboratory to develop an initial set of material model parameters to enable physics-based penetration simulations of high-fidelity brick and mortar masonry wall models. A search of publicly released literature turned up not much concerning modeling and simulation of weapon effects against brick and mortar targets. The characteristic of concrete under dynamics load has been studied in detail however the investigation of dynamic material properties of brick and mortar is in early stages [3]. What has been historically employed to investigate the dynamic characteristic of concrete includes theoretical method, experimental method and the numerical simulation. It has been shown that numerical stimulation is a cost-effective method and can provide more information of process history for sophisticated analysis than experimental method. Nevertheless, the data from experiments were crucial because on the one hand any modern analysis and stimulation computation should necessarily be validated by those come from real range tests, on the other hand the material parameters which are of vital importance to obtain a reasonable and compelling result must be furnished by or refer to experimental data [4]. The experimental exploration indicates that brick and mortar joint act similarly as concrete. Many material models are proposed to describe the behaviour of concrete, which are able to apply to solution of simulating behaviour of masonry reasonably. Li et al. [5] investigated the response mode of masonry subjected to vented gas explosion through experiment and simulation, in which the anisotropic material model *MAT_96 (MAT_BRITTLE_DAMAGE) has been adopted. The material model has been developed by Govindjee et al. [6]. Meyer explored profoundly the potential of the HJC model to apply in simulation of penetrations, which was initialled by Holmquist and Johnson in 1993 [3].